EFFORTS TO ENHANCE CRITICAL THINKING SKILLS AND ATTITUDES TOWARD SCIENCE THROUGH THE PROBLEM-BASED LEARNING MODEL - Talia Ananda; Azhar; Fakhruddin Z (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2026)
The development of students’ critical thinking skills and attitudes toward science is essential for strengthening the quality of education in Indonesia. However, observations at a senior high school revealed that students demonstrated limited critical thinking abilities and low attitudes toward science, particularly in physics learning. This study aimed to describe the implementation of the Problem-Based Learning model and to examine its effectiveness in improving students’ critical thinking skills and attitudes toward science. The research employed a classroom action research design consisting of two cycles, each involving planning, action, observation, and reflection. Data were collected through tests of critical thinking skills and questionnaires measuring attitudes toward science. The findings showed substantial improvements in all five indicators of critical thinking, with stronger gains observed in the second cycle following instructional refinements. Students’ attitudes toward science also improved across all indicators, including interest, learning activities, perceived importance of science, and interest in pursuing science-related careers. The results indicate that the Problem-Based Learning model successfully increased students’ engagement, reasoning ability, and positive perceptions of science. The study implies that implementing learning strategies centered on real-world problem solving can effectively enhance both cognitive and affective aspects of science learning.